PENGARUH PENGALAMAN KONSUMEN DAN CITRA MEREK LOKALTERHADAP MINAT BERKUNJUNG ULANG DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI (Studi pada pelangganwarung kopi dengan brand lokal di Kota Pontianak) - B1021161036, HENNI OKTAVIANI (Jurnal Manajemen Update, 2020)
ABSTRACT    This reseach is conducted to find out the effect of consumer experience variables, local brand image, and customer satisfaction on revisit intention to a coffee shop with a local brand in Pontianak. This research is included in descriptive research with survey method. The type of research used in this research is causal associative research, and data collection techniques are through distributing questionnaires through the google from application. The population in this study were all consumers who had visited coffee shops with local brands in Pontianak City such as AmingCoffe, Asiang Kopi, and Bang Edi Coffee. The number of samples in this study was 100 respondents. Sampling was conducted using non-probability sampling techniques with purposive sampling method and analysis tools, namely path analysis (path analysis).The results showed that the variables of consumer experience, local brand image, and customer satisfaction significantly influence the interest in a repeat visit. The ability of these three variables in explaining their influence on the behavior of revisiting interest was 55.9% while the remaining 44.1% was explained by other factors outside the research model.Keywords: Consumer experience, local brand image, customer satisfaction, revisit intention.DAFTAR PUSTAKA Amilia, S. (2017). Pengaruh Citra Merek, Harga, dan KualitasProdukterhadap Keputusan PembelianHandphoneMerekXiaomi di Kota Langsa.JurnalManajemen Dan Keuangan, Vol.6, No.1, Mei 2017.Azhari Iqbal, M., Fanani, D., &MawardiKholid, M. (2015). PengaruhCustomer                   ExperienceTerhadapKepuasanPelanggan Dan LoyalitasPelanggan (Survei Pada PelangganKfc Kawi Malang). JurnalAdministrasiBisnis (JAB)|Vol. 28 No. 1 November 2015. Behboudi, I. & Hosseini, S. H. K. (2017). Brand trust and image: Effects on customer satisfaction.International Journal of Health Care Quality Assurance. Retrieved from https://doi.org/10.1108/IJHCQA-04-2016-0054.Bigne, J. E., Sanchez, M. I., & Sanchez, J. (2001). Tourism image, evaluation variables and after purchase behaviour: Inter-relationship. Tourism Management, 22, 607-616.Chotimah, S., &Wahyudi, D. H. (2019). PengaruhPerceived ValueTerhadapRevisit      Intention: MediasiCustomer Satisfaction Pada PengunjungJawa Timur Park I Batu. EKOBIS – EkonomiBisnis Vol. 24 No. 1 | Mei 2019 | Halaman 1-11.Dewi, I.A.I., &Laksmidewi, D. (2015). PengaruhCustomer ExperiencesTerhadapRevisit IntentionDenganMediasiLearning In Museum Dan Visitor Satisfaction Di Museum Wayang. JurnalManajemen [Vol. 12 No. 2 November 2015.Gentile, C., Spiller, N., &Noci, G. 2007. How to sustain the customer experience: An overview of experience components that co-create value with the customer. European management journal, 25(5), 395-410. https://doi.org/10.1016/j.emj.2007.08.005 Ghozali, I. (2011). AplikasiAnalisis Multivariate dengan Program IBM SPSS 19. Semarang: Badan penerbitUniversitasDiponegoro.Hadiyono, N., &YonathanPalumian, Y. (2019). PengaruhFasilitas Dan Citra MerekTerhadapNiatPembelianUlangProduk Starbucks Di Surabaya. Agora Vol. 7, No. 2, (2019).Han Heesup, et al. (2019). Impact of core-product and service-encounter quality, attitude, image, trust and love on repurchase: Full-service vs low-cost carriers in South Korea. International Journal of Contemporary Hospitality Management, https://doi.org/10.1108/IJCHM-05-2018-0376Harsiska, N. (2019). Pengaruh Word Of Mouth Dan AksesibilitasTerhadap Destination Image Dan Dampaknya Pada MinatBerkunjungUlang (Studi Pada ObjekWisata Kota Singkawang).UniversitasTanjungpura, Indonesia.Hosseini, S.H.K., &Behboudi, L. (2017). Brand trust and image: effects on customer satisfaction. International Journal of Health Care Quality Assurance, Vol. 30 Issue: 7, pp.580-590, https://doi.org/10.1108/IJHCQA-04-2016-0054.Isnaini, P.R., &Abdillah, Y. (2018). Pengaruh Citra MerekDestinasiTerhadap Keputusan Berkunjung Dan KepuasanPengunjung Serta Dampaknya Pada MinatKunjungUlang (Survei Pada Pengunjung Taman Rekreasi Selecta Kota Batu Yang TermasukDalamKategoriGenerasi Millennial).JurnalAdministrasiBisnis (JAB)|Vol. 55 No. 2 Februari 2018.Japarianto, E., (2019). PengaruhRetail Service QualityTerhadapMinatBerkunjungUlang Mall Di Surabaya MelaluiPerceived Quality Dan Customer SatisfactionSebagaiVariabelIntervening.JurnalManajemenPemasaran, Vol. 13, No. 1, April 2019, 17─26.Keller, K.L. (1993). Conceptualizing, Measuring, and Managing Customer-Based Brand Equity Author. Journal of Marketing, Vol. 57, No. 1 (Jan., 1993)Kotler, Philip & Keller, K.L. (2007). Manajemen Pemasaran, Edisi 12, Jilid 1. Jakarta: PT.IndeksKotler, P., & Keller K.L. (2008). ManajemenPemasaran-Edisi 12: Jilid 1. Indonesia: PT IndeksKotler, P., & Keller K.L. (2009). ManajemenPemasaran-Edisi 13: Jilid 1. Indonesia: PenerbitErlanggaKotler, Philip and Keller K.L. (2012). Marketing Management. 14st edition. Prentice Hall: New Jersey.Kuncoro, M. (2013). MetodeRisetUntukBisnis&Ekonomi: BagaimanaMeneliti dan MenulisTesis. Indonesia: PT. GeloraAngkasaPratamaMeyer, C., &Schwager, A. (2007). Understanding customer experience. Harvard Business Review, 2, 117-126. https://hbr.org/2007/02/understanding-customer-experience Nasermoadeli, Amir., Choon-Ling, Kwek., Maghnati, Farshad. 2012. Evaluating the Impacts of Customer Experience on Purchase Intention. International Journal of Business and Management vol.8, No.6 2013.Nuraeni, Bellinda Sofia. (2014). AnalisisFaktor-Faktor Yang MempengaruhiMinatKunjungUlangWisatawan Museum Ranggawarsita Semarang. JurnalBisnis STRATEGI Vol. 23 No. 1 Juli 2014.Ongkowidjojo, M. (2018). Pengaruh Citra Merek Dan Kualitas Yang DipersepsiKonsumenTerhadapKepuasanPelangganGrabcarDi Surabaya. AGORA Vol. 6, No. 2, (2018).Petrik, J.F., Morais, D.D., &Norman,W.C. (2001). An Examination Of The Determinants Of Entertainment Vacation’ Intentions To Revisit, Journal Of Travel Research, 40 (1), 41-48.Pramudita, Y.A., &Japarianto, E. (2013). Analisa PengaruhCustomer Value dan Customer ExperienceterhadapCustomer Satisfaction di De Kasteel Resto Surabaya. JurnalManajemenPemasaran Petra Vol. 1, No. 1, (2013).Pranoto, G. R., &Subagio, H. (2010). Analisa PengaruhCustomer ExperienceTerhadapCustomer Satisfaction Pada KonsumenDi Rosetta’s Cafe & Resto Surabaya. JurnalManajemenPemasaran Petra. Prastyaningsih, Suyadi&Yulianto, E. (2014). PengaruhCustomer ExperienceTerhadapRepurchase Intention (Survei pada Konsumen KFC Di LingkunganWarga RW 3 DesaKandangrejo, Kedungpring, Lamongan). JurnalAdministrasiBisnis (JAB)|Vol. 16 No. 1 November 2014Prayitno, Y. &Sutanto, E.M. (2018). AnalisisPengaruhKualitasProduk, KualitasLayanan, Dan Citra MerekTerhadapKepuasanKonsumen Bakmi Raja Nikmat Cabang Royal Plaza Surabaya. AGORA Vol. 6, No. 2, (2018).Priansa, D.J. (2017). PerilakuKonsumen: DalamPersainganBisnisKontemporer. Bandung: AlfabertaRositasari, et al. (2019). KomunikasiPemasaranTomcir (Atom Kocir) DalamMembangunEksistensiSebagai Brand Lokal Cirebon (StudiDeskriptifKualitatifKomunikasiPemasaran Pada Tomcir (Atom Kocir) Di Kota Cirebon). JURNAL SIGNAL Volume 7 No. 1, Januari - Juni 2019 | IlmuKomunikasi – FISIP.Saputri, N.A.H. (2019). Pengaruh Customer Experience Terhadap Electronic Word Of Mouth Dengan Customer Satisfaction SebagaiVariabelMediasi(Studi pada KonsumenChingu Cafe Yogyakarta).Universitas Negeri Yogyakarta, Indonesia.Scmitt, Be. H. (1999): Experiential Marketing, Journal of Marketing Management, 15:1-3, 53-67. http://dx.doi.org/10.1362/026725799784870496Sekaran, U. (2006). Metode Penelitian Bisnis. Jakarta: Salemba Empat.Senjaya, et al. (2013). PengaruhCustomer Experience Quality TerhadapCustomer Satisfaction & Customer Loyalty Di KafeExcelsoTunjungan Plaza Surabaya: Perspektif B2c. JurnalManajemenPemasaran Petra Vol. 1, No. 1, (2013).Simarmata, B. (2016). Pengaruhcitramerek dan dayatarikiklanterhadapkeputusanpembeliankonsumenproduksmartphone Samsung pada mahasiswaStieItmi Medan. JurnalIlmiahIntegritas, 2(1), 1-18. http://www.Jurnalmudiraindure.com/wp-content/uploads/2016/08/PENGARUH-CITRA-MEREK-DAN-DAYA-TARIK-IKLAN-TERHADAP. Siregar, S. (2017). StatistikParametrikuntukPenelitianKuantitatif: DilengkapidenganPerhitungan Manual dan Aplikasi SPPS Versi 17. Jakarta: BumiAksaraSmilansky, Shaz. 2009. Experiential Marketing : A Practical Guide To Interactive Brand Experiences. London and Philadelphia: Kogan PageSugiyono (2012). MetodePenelitianKuantitatif, Kualitatif, dan R&D. Indonesia: AlfabetaSolimun, (2011). AnalisisVariabelModerasi dan Mediasi. Program StudiStatistika FMIPA universitasBrawijaya. Malang.Sugiyono (2017). MetodePenelitianBisnis: PendekatanKuantitatif, Kualitatif, Kombinasi, dan R&D.Edisi 3, Bandung: AlfabetaSunyoto, D. (2014). Dasar-Dasar ManajemenPemasaran – Konsep, Strategi, dan Kasus. Yogyakarta: CAPS (Center of Academic Publishing Service)Tjiptono, F. (2014). Pemasaran Jasa – Prinsip, Penerapan, dan Penelitian. Yogyakarta: C.V ANDI OFFSETTjiptono, F. (2016). PemasaranEsensi&Aplikasi. Yogyakarta: C.V ANDI OFFSETVentura, Y. C. (2018). PengaruhPengalamanPengunjung, Citra Destinasi Dan Sosial Media MelaluiKepuasanPengunjungTerhadapMinatBerkunjung Kembali Pada WisataTelagaSarangan Di KabupatenMagetan. UniversitasJember, Indonesia.Wulandari, K. (2015). AnalisisPersepsiPelangganAtasDimensiKualitas Jasa TerhadapKepuasanPelanggan Dan NiatBeliUlang. JurnalAdministrasiBisnis (2015), Vol.11, No.1: hal. 84–100, (ISSN:0216–1249).Yuniawati, Y., &Finardi, A.D.I. (2015). PengaruhCustomer ExperienceTerhadapRevisit IntentionDi Taman WisataAlamGunungTangkubanPerahu.Tourism And Hospitality Essentials (The) Journal, Vol.Vi.Website:https://amingcoffee.com/https://kumparan.com/hipontianak/3-rekomendasi-coffee-shop-di-pontianak-yang-gunakan-kopi-lokal-1rR0KCyB3WShttps://tanilink.com/bacaberita/138/kopi-dengan-pengolahan-basah-dapat-mendukung-tumbuhnya-bisnis-kopi-dalam-negeri/https://kumparan.com/hipontianak/7-fakta-warung-kopi-asiang-di-pontianak-yang-legendaris-1rHoQiJTDSyhttps://kumparan.com/hipontianak/wali-kota-pontianak-kenalkan-kopi-robusta-lewat-kopi-bang-edi-1rFWGfOeOtehttp://quantpsy.org/sobel/sobel.htm